(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This article explores the importance of studying and heritage of our ancestors using a synergistic methodology. The author emphasizes that such an approach is of great importance for finding rational solutions to modern problems in the context of globalization. The article critically assesses the ideological interpretation of past research and suggests using modern philosophical methodology to better understand our identity. It also highlights the contribution of our ancestors to world civilization and the importance of educating young people about a rich historical past in order to create a sense of national pride. In addition, the article points to the significance of the philosophical views and discoveries of our great thinkers in the development of modern science. Overall, this article provides a valuable scientific and theoretical source for future research and progress.